Penguatan Pendidikan Kewarganegaraan dalam Membina Nasionalisme Bagi Mahasiswa UPN Veteran Jawa Timur - Adelia Putri Septia Nugroho; Birigitta Ardiana Diva Azzahra; Kinanti R Hayati; Sultan Fatahillah Fitrah Rahardjo (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Education is an important component of a country. Education is one of the obligations of every citizen to advance the progress of thought and advance the progress of the nation. The Civics education is a general compulsory subject in Indonesia. This study aims to explore the impact of globalization on nationalism at UPN â€œveteranâ€ schools in East Java and the importance of citizenship education in the campus environment. In this study, we used qualitative methods, interviewed 3 informants and distributed questionnaires to 50 additional informants. All of them were â€œveteranâ€ UPN students from East Java. The results of interviews and surveys conducted resulted in the conclusion that love for the nation and also having a sense of nationalism must be instilled in the younger generation through citizenship education in the educational environment. This will help achieve the goals of civics education and make citizens aware of their rights and obligations as members of the Indonesian state. In this way the quality of the implementation of civics education will further increase the awareness of the younger generation that they are the next generation of the Indonesian nation.Â